Pengembangan Modul Berbasis Discovery Learning Materi Momentum Dan Impuls - Azmi Sukroyanti (GRAVITY EDU : Jurnal Pembelajaran dan Pengajaran Fisika, 2021)
This study aims to determine the eligibility criteria for discovery learning based modules in physics for grade X high school students. This study uses a (research and development method). The development model used in this research is the ADDIE development model. In this study, only three stages were used, namely analysis, design and development. The instrument used was an expert validation questionnaire. The results obtained by each score on expert validators who have different values ​​include, validator presentation 1, 98.76% in the very good or very suitable category, validator 2, with a presentation of 81.48% in the good or feasible category. used, validator 3 with a presentation of 70.37% in the category of good or suitable for use, and the presentation of validator 4, 88.88% with the category very good or fit for use. So it can be concluded that the product or module developed is suitable for use at the high school level, especially in the physics subject for class X SMA